Linguistic Characteristics of the Terminological System of Technical Sciences (Eurasian Journal of Philology Science and Education, 2024)
The article is devoted to the linguistic description of the terminological system of technical sciences, namely the branches of mechanics and mechanical engineering, which provided for the classification of terms of these industries in terms of type and content (structural and semantic), analysis of the process of their terminologization.In the course of the study, the ways of creating terms in the field of technology in general were highlighted, and the process of naming new concepts that have arisen in the field of science and technology was grouped by stages.The article defines the following features of the terminology of the branches of mechanics and mechanical engineering: the synthetic (morphological) method is intensively used, that is, the creation of a term using suffixes; the composition of terms created by the analytical (syntactic) method is diverse; such types of analistic (syntactic) method as word composition and word combination are often used; terms formed by word combinations, they are based on the method of structural, semantic and syntactic calculus from the Russian language; terminological names created by the lexico-semantic (conversion) method arise as a result of the expansion of the meaning of the original words of the Kazakh language through metaphorical use based on national cognition; in these dictionaries there are different types of use of variants; such uses are due to various linguistic and extralinguistic factors.Methods of selection, systematization, classification into lexico-semantic groups, structural (morphemic) analysis, description, structural-semantic grouping, component analysis, synchronous analysis, deductive and inductive analysis, linguistic interpretation, interdisciplinary comparison, comparison were used in the course of the study.The results of the article contribute to the improvement of scientific-theoretical, applied-practical and methodological foundations for the development of the terminological system of branches of technical sciences and the terminological fund of the Kazakh language as a whole, that is, the study is valuable for writing scientific research, compiling various dictionaries (registry, explanatory, etc.), compiling various methodological guidelines for terminological work, organizing courses advanced training of specialists in the branches of technical sciences, teaching staff, journalists, lectures on terminology in higher educational institutions.Keywords: technical sciences, term, dictionary, unification, duplication.